2013
DOI: 10.1080/10503307.2013.847989
|View full text |Cite
|
Sign up to set email alerts
|

Identification of caregivers at greatest risk of major depression in two prevention studies

Abstract: RESULTS implicate the utility of emotional distress for depression screening and the need to develop tailored interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
7
1
Order By: Relevance
“…To our knowledge, this is the first report identifying RAR characteristics associated with depression symptom severity in strained caregivers, who are an important group known to be at elevated risk for developing depression (Ballard et al ., ; Beach et al ., ; Blanco et al ., ; Cuijpers, ; Joling et al ., , ). We found that greater night‐time sleep fragmentation and having the least steep/'square‐like’ RAR curves (those in the lowest quartile of RAR beta values) were, independently of each other, associated with having a greater burden of depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first report identifying RAR characteristics associated with depression symptom severity in strained caregivers, who are an important group known to be at elevated risk for developing depression (Ballard et al ., ; Beach et al ., ; Blanco et al ., ; Cuijpers, ; Joling et al ., , ). We found that greater night‐time sleep fragmentation and having the least steep/'square‐like’ RAR curves (those in the lowest quartile of RAR beta values) were, independently of each other, associated with having a greater burden of depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Informal (unpaid) providers of care for a person with a disability or impairment form such a group, where the risk for major depressive disorder is very high (Ballard et al ., ; Cuijpers, ; Joling et al ., , ), especially when caregivers are already experiencing caregiving‐related strain or distress (Beach et al ., ; Blanco et al ., ). Several lines of evidence suggest that objectively measured RAR disturbances may mark depression symptom severity in dementia caregivers.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, our findings (regarding the factors that attenuated the white matter-caregiving strain association) can be interpreted within the context of existing literature and current conceptual frameworks. Depression, a known consequence of strain in caregivers (4, 10), is often conceptualized as a consequence of white matter disease (11-13). Depression symptoms attenuated the association of interest, potentially because depression is an intermediate (mediator) between white matter pathology and caregiving strain, or a downstream consequence of caregiving strain.…”
Section: Discussionmentioning
confidence: 99%
“…Replacing older adults' informal caregiving services with skilled or unskilled workers, respectively, would cost an estimated 162 or 56 billion dollars per year (9). Since caregiver's depression risk is potentiated by strain (4) and emotional distress (10), caregivers with these characteristics represent those in the greatest need of pathophysiologically informed interventions for depression prevention.…”
mentioning
confidence: 99%
“…In another study, Vázquez et al [85] found signiicant diferences between a ive-session cognitive-behavioral intervention and a usual care control group in the reduction of depressive symptomatology (d = 1.33) and the incidence of depression (3.4% vs. 22.0%) at 12-month follow-up (see Figure 2). Both interventions were efective regardless of the condition of the person cared for [86,87]; those changes in depressive symptomatology were also clinically signiicant [88] and homework tasks played a fundamental role in the reduction of depressive symptomatology [89].…”
Section: Professional Support When Psychopathological Symptoms Occurmentioning
confidence: 99%